Education for Rural Transformation in Thailand: Perspectives on Policies and Practices - Bhola, Harbans (Journal of Education and Research, 2015)
To engage meaningfully on the subject of “Education for Rural Transformation,” it is essential first to understand the concept of the “Rural Condition” as well as of “Education” – which is influenced by social, economic, political, technological and cultural factors. There are two additional complexities in that the “Rural Condition” itself is not something stable and absolute but is indeed in perpetual flux across Time and Place; and that the rural condition is inconceivable without at the same time understanding the “Urban Condition.” Concomitantly, “Education” itself will have to undergo transformation to serve as the lever of rural and urban transformations. Rural and urban transformations today have come to acquire one globally-focused mission, dealing with three objectives: mitigation of global warming, pursuing sustainable development and committing to poverty alleviation, in both rural and urban habitations. For “Planned Action” informed by the general conceptual framework constructed here, the general must be contextualized in each particular setting of time, space and locality – responding to a specific “Political Economy”; to policy processes such as formulation, planning, mobilization, implementation and evaluation; and configurations of agents and adopters of planned actions. Finally, the “Logic of Action” must come from the dialectics between the structural and the instructional.